2004
DOI: 10.1038/sj.sc.3101516
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic moderate systemic hypothermia reduces TUNEL positive cells following spinal cord injury in rat

Abstract: Study design: A standardized animal model of contusive spinal cord injury (SCI) with incomplete paraplegia was used to test the hypothesis that moderate systemic hypothermia reduces neural cell death. Terminal deoxynucleotidyl transferase [TdT]-mediated deoxyuridine triphosphate [dUTP] nick-end labeling (TUNEL) staining was used as a marker of apoptosis or cell damage. Objective: To determine whether or not moderate hypothermia could have a neuroprotective effect in neural cell death following spinal cord inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 47 publications
2
25
0
6
Order By: Relevance
“…This difference in data shows that cooling intervention immediately post-SCI has strong therapeutic effect. This confirms reports by other workers who found that cooling therapy improves recovery after SCI in rats (Shibuya et al, 2004;Morino et al, 2008). It should be stressed that the BBB method can be useful for measuring locomotion, whereas the current force plate method can be useful for measuring postural support.…”
Section: Discussionsupporting
confidence: 91%
“…This difference in data shows that cooling intervention immediately post-SCI has strong therapeutic effect. This confirms reports by other workers who found that cooling therapy improves recovery after SCI in rats (Shibuya et al, 2004;Morino et al, 2008). It should be stressed that the BBB method can be useful for measuring locomotion, whereas the current force plate method can be useful for measuring postural support.…”
Section: Discussionsupporting
confidence: 91%
“…As with necrosis, apoptotic cell death appears to be sensitive to postinjury hypothermic treatment strategies. Using terminal deoxynucleotidetransferase-mediated dUTP-biotin nick end labeling (TUNEL) staining, DNA fragmentation has been found to be reduced by hypothermia in severe TBI (Brodhun et al, 2001), transient global ischemia (Zhang et al, 2001b), transient focal ischemia (Inamasu et al, 2000a;Phanithi et al, 2000;Prakasa Babu et al, 2000), and SCI (Shibuya et al, 2004). Levels of caspase 3, an important initiator of apoptotic cell death, are highly sensitive to hypothermic treatment (Phanithi et al, 2000;Van Hemelrijck et al, 2005;Lotocki et al, 2006), as is cytochrome c release Zhao et al, 2004Zhao et al, , 2005Zhao et al, , 2007.…”
Section: Neuronal Cell Deathmentioning
confidence: 99%
“…By varying the compression time from 10 to 30 min, it is possible to produce models of different severity from mild incomplete paralysis to complete paralysis. 8 Process of functional recovery. After complete spinal cord transection in cats and rats, the occurrence of bilaterally symmetrical locomotive activities in the hindlimbs (walking-like neural activity) is a well known observation.…”
Section: Animal Models Of Incomplete Spinal Cord Injurymentioning
confidence: 99%